Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoît, J., Dagnogo, D.S., Savard, J. & Savard, S. (2021, mise à jour 2025). Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops. ca/repertoire_pratiques_novatrices.html fs-code-orig: Benoit-2025b

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoit, J., Dagnogo, D.S., Savard, J., & Savard, S. (2021, mise à jour 2025). Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html. fs-code-orig: Benoit-2025c

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance
The standard can be bought from this web page.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité
La norme peut être achetée à partir de cette page web.

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)
fs-ref-orig: Ibrahim, N., Benoît, J. & Savard, J. (2025). Practice 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_ innovative_practices.html fs-code-orig: Ibrahim-2025

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

Francophone patients - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)
fs-ref-orig: Réseau des services de santé en français de l'Est de l'Ontario. (2022). La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés [infographie]. fs-code-orig: Réseau des services de santé en français de l'Est de l'Ontario-2022a (PDF à séparer)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)
fs-ref-orig: Santé Ontario, Réseau des services de santé en français de l'Est de l'Ontario et Santé Canada. (2022). Données sur les soins de longue durée en français : équipe Santé Ontario du Grand Fleuve [infographie]. fs-code-orig: Santé Ontario-2022a

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)
fs-ref-orig: Sauvé-Schenk, K., Savard, J., Prud’homme, D., Durand (Chiocchio), F. et Delluc, C. (2021). Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français. Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire. fs-code-orig: Sauvé-Schenk-2021

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)
fs-ref-orig: van Kemenade, S., Michel, J.N., Savard, J. & Benoît, J. (2021, mise à jour 2025). Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: van Kemenade-2025a

Création d'une grille d'observation pour simulations sur l'offre active de services de santé en français - Vincent, Coralie; Bodnaruc, Alexandra Maria; Kengneson, Cris-Carelle; Savard, Jacinthe; Giroux, Isabelle (Reflets, 2021)
Au Canada, il fut démontré que les communautés francophones vivant en situation linguistique minoritaire éprouvent des difficultés à se prévaloir de services sociaux et de santé dans leur langue de préférence, ce qui peut négativement affecter la qualité et la sécurité des services. L’offre active est une pratique visant à contrer les effets de la minorisation linguistique en invitant, de manière proactive et dès le premier contact, les bénéficiaires à s’exprimer dans la langue officielle de leur choix. Il n’existe actuellement aucun outil validé permettant l’évaluation de cette compétence auprès des futurs professionnels des domaines de la santé et des services sociaux. Cet article présente les étapes de création et de validation de Grille d’observation des indicateurs de compétence la en offre active de services en français, laquelle vise à soutenir les programmes de formation dans l’enseignement et l’évaluation de cette compétence au moyen de simulations. Mots-clés : minorités linguistiques, offre active de services en français, langue et services, qualité des soins, formation professionnelle en santé et service social, grille d’observation, validation